Consistency of the Indonesian Ulama Council in Using Istiá¹£lÄá¸¥ as a Method for Legal Istinbath - Azwar, Zainal; Rinaldi, Farid Afif (Institut Agama Islam Negeri Curup, 2024)
This article aimed to analyze the consistency of the Indonesian Ulama Council (MUI) in using Istiá¹£lÄá¸¥ (public interest) as a method for legal determination when issuing fatwas. There were fatwas where the use of Istiá¹£lÄá¸¥ was very evident with the goal of safeguarding human lives, while in other fatwas, the opposite seemed to be the case. The objective of this study was to analyze the background of the emergence of fatwas and the consistency of MUI in using Istiá¹£lÄá¸¥. This article is a normative legal study with an usul al-fiqh (principles of Islamic jurisprudence) approach. The data used represented secondary data in the form of Fatwa No. 14 of 2020 and Circular No.: Kep-1702/DP MUI/IX/2020 as the primary legal materials. Other legal materials, such as books and scholarly articles, were also used. The data obtained were analyzed descriptively using the techniques of reduction, display, and verification. The research results indicated the following: first, the emergence of both ijtihad products was caused by two conflicting government objectives; the desire to prohibit gatherings during worship and the desire to allow gatherings during regional elections. Second, these fatwas and circulars demonstrated inconsistency in the use of Istiá¹£lÄá¸¥. In Fatwa No. 14 of 2020, MUI showed consistency in using Istiá¹£lÄá¸¥. On the other hand, MUI appeared inconsistent in using the same method even though the primary goals of both ijtihad products were the same, preventing the spread of Covid-19 through mass gatherings.